2013
DOI: 10.1016/j.jviromet.2012.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies against Caprine arthritis-encephalitis virus epitopes in the p28 and p55gag viral proteins

Abstract: The genome of the Caprine Arthritis-Encephalitis Virus (CAEV) encodes the polycistronic precursor protein p55(gag). Proteolytic cleavage of p55(gag) generates the viral core proteins. Some studies suggest that the CAEV p55(gag) protein contains epitopes or antigenic determinants for these core proteins. This work reinforces this hypothesis and demonstrates that monoclonal antibodies (MAbs) that are directed against the capsid protein (p28) of CAEV are also reactive against the precursor p55(gag) protein and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The IDEXX ELISA kit, which was used in our study, uses a mixture of the transmembrane protein (TM ENV gene) and recombinant p28 protein (GaG gene) for the detection of the infection as a multi-antigen approach. It was reported that monoclonal antibodies against p28 are also reactive against p55 (gag) protein and the intermediate cleavage products, p44, p36, and p22 [ 38 ]. The antibody response was significantly higher among arthritic than asymptomatic goats [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IDEXX ELISA kit, which was used in our study, uses a mixture of the transmembrane protein (TM ENV gene) and recombinant p28 protein (GaG gene) for the detection of the infection as a multi-antigen approach. It was reported that monoclonal antibodies against p28 are also reactive against p55 (gag) protein and the intermediate cleavage products, p44, p36, and p22 [ 38 ]. The antibody response was significantly higher among arthritic than asymptomatic goats [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IDEXX ELISA kit, which was used in our study, uses a mixture of the transmembrane protein (TM ENV gene) and recombinant p28 protein (GaG gene) for detection of the infection as a multi-antigen approach. It was reported that monoclonal antibodies against p28 are also reactive against p55 (gag) protein and the intermediate cleavage products, p44, p36 and p22 [38]. The antibody response was significantly higher among arthritic than asymptomatic goats [28].…”
Section: Discussionmentioning
confidence: 99%
“…The IDEXX ELISA kit, which was used in our study, uses a mixture of the transmembrane protein (TM ENV gene) and recombinant p28 protein (GaG gene) for detection of the infection as a multi-antigen approach. It was reported that monoclonal antibodies against p28 are also reactive against p55 (gag) protein and the intermediate cleavage products, p44, p36 and p22 [38]. The antibody response was significantly higher among arthritic than asymptomatic goats [28].…”
Section: Discussionmentioning
confidence: 99%